To find the function rule in slope-intercept form \( f(x) = mx + b \), we need to first determine the slope \( m \) and the y-intercept \( b \) from the given points.
The two points provided are \((-2, 2)\) and \((4, -1)\).
- Calculate the slope \( m \):
The formula for the slope \( m \) between two points \((x_1, y_1)\) and \((x_2, y_2)\) is:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Substituting the coordinates of the points:
\[ m = \frac{-1 - 2}{4 - (-2)} = \frac{-3}{4 + 2} = \frac{-3}{6} = -\frac{1}{2} \]
So, the slope \( m \) is \(-\frac{1}{2}\).
- Use the slope-intercept form to find \( b \):
We can use one of the points to solve for \( b \). Let's use the point \((-2, 2)\):
Using the slope-intercept equation \( y = mx + b \):
\[ 2 = -\frac{1}{2}(-2) + b \]
Calculating the right side:
\[ 2 = 1 + b \]
Now, solving for \( b \):
\[ b = 2 - 1 = 1 \]
- Write the complete function:
Now that we have \( m = -\frac{1}{2} \) and \( b = 1 \), we can put it all together:
\[ f(x) = -\frac{1}{2}x + 1 \]
So, the function rule in slope-intercept form is:
\[ f(x) = -\frac{1}{2}x + 1 \]